Penentuan Jarak Optimal Kapal Tradisional Pelayaran Rakyat Untuk Peningkatan Daya Saing Layanan Transportasi Laut - Akmal Lazuardy (Politeknik Negeri Madura, 2017)
Indonesia has complicated challenge in logistics system due to the archipelagic form. It requires established logistics system with marine transportation plays important role in it. There are two types of Indonesian marine transport services: PELNAS (Pelayaran Nasional) or national shipping is a more modern transportation services. It is clear that PELNAS more preferable to consumer with its sophisticated outfitting, powerful engine, faster speed, and faster cargo handling. On the other hand, PELRA or traditional shipping is a marine transportation services up to 500 gross tonnages managed by lower economic class using traditional ship made from ironwood. Therefore, it has major limitation especially in its capacity as well as its sailing range. These two marine transportation services are in competition and, without a doubt; PELNAS excelled PELRA in any aspects. However, the fact that PELRA still existed today, might indicates that PELRA already has established small niche market in Indonesia. This research seek to determine how far its operating distance to answer why PELRA rooted specific market in order to stand a chance from competition with PELNAS. It turns out that PELRA are more cost-efficient than PELNAS under 432,05 nautical miles with critical unit cost: Rp. 9.016 ,74 per tonnemiles. This distance is equivalent to Jakarta – Surabaya (384 nautical miles), Jakarta – Palembang (355 nautical miles), and Surabaya - Sampit (360 nautical miles). The result is relevant as those routes are commonly serviced by PELRA with traditional ship rather than PELNAS with its advanced modern ship.